Potash regime for restoration of disturbed lands in the Far North - Iglovikov Anatoly (E3S Web of Conferences, 2020)
Disturbed soils of the Far North, underlain by permafrost, have extremely low fertility and were formed according to natural and climatic conditions. These soils and the vegetation cover formed on them are very vulnerable to destructive anthropogenic impacts associated with the industrial development of the North. To restore vegetation cover, agrotechnical techniques are used, including the use of various fertilizers. This article will address issues related to changes in the content of potassium in various agricultural techniques at the biological stage of recultivation in the Far North. Agromeliorative techniques increased the accumulation of potassium in the herbage, therefore, perennial grasses consume a large amount of potassium, strengthening their ecological plasticity. It is established that agromeliorative techniques play a crucial role in providing long-term grasses with available potassium. Potassium is consumed by perennial herbs throughout life. This fact should be taken into account when determining the rates of potash fertilization to maintain a stable herbage at the biological stage of reclamation and accelerate the restoration of natural cover.